Water use, water limitation, and water use efficiency in a Eucalyptus plantation - Stape, Jose Luiz; Binkley, Dan; Ryan, Michael G.; Do Nascimento Gomes, Antonio (Bosque (Valdivia), 2004)
Millions of hectares of Eucalyptus are intensively managed for wood production worldwide, but the ecophysiology of resource limitation on growth remains poorly quantified. We investigated the production ecology of a 3.4- to 5.4 year-old plantation of clonal Eucalypus grandis x urophylla in northeastern Brazil on a sandy Oxisol during two years (one wet, and one with normal rainfall). We measured wood production and estimated water use (transpired water) in control and irrigated treatments. Water supply limited growth; wood biomass increased from 36.6 Mg ha–1 for both treatments to 107.0 and 141.0 Mg ha–1 after 2 years for the control and irrigated plots. Across both years, irrigation increased wood productivity by 52% (42.8 Mg ha–1 yr–1 versus 28.1 Mg ha–1 yr–1). Water use was similar between the control and irrigated treatments during the wet year, but irrigation increased water use by 37% in the normal rainfall year. The efficiency of water use (wood production per m3 of transpired water) in the control treatment increased from the normal year (1.8 kg wood/m3 of water) to the wet year (3.2 wood/m3 of water), and irrigation increased water use efficiency by 18% in the wet year, 75% in the normal year, and 32% across both years. In combination with prior work on water use efficiency across a geographic gradient in rainfall, these irrigation results indicate that increasing water use efficiency should be expected with increasing water use by Eucalyptus.